Development and validation of a voltammetric method for quantifying lead in rat blood - Irias Zelaya, Carlos Roberto; Madrid Mendoza, Maria fernanda; Villanueva Salas, Ana María; Rojas Tamata, Karen; Carpio Carpio, José M.; Villanueva Salas, José A; Choquenaira-Quispe, Celia (LACCEI, 2024)
Lead is a toxic heavy metal that does not have any biochemical or physiological role. On the contrary, it produces multisystemic alterations that could lead to the death of a living being. Although there are some standardized methods for lead quantification, electroanalytical techniques are often presented as a rapid, sensitive, and economical alternative. Although there are standardized methods for lead quantification, electroanalytical techniques are presented as a rapid, sensitive, and economical alternative. In this investigation, we developed and validated a voltammetric method for quantifying lead in blood. The voltammetric method was used to quantify lead in rat blood. The results showed a linear relationship with a determination coefficient (R2) greater than 0.999. The method was precise with variation coefficients lower than 2.7% and accurate with recovery percentages close to 100%. The limits of detection and quantification were 0.000134 and 0.001433 mg/L, respectively. The obtained results propose an optimized alternative method for quantifying lead in blood with reliable results quickly.